Analysis of genetic variation in unisexual and bisexual lizard species of the genus Leiolepis from Southeast Asia - Malysheva, D. N.; Darevsky, I. S.; Tokarskaya, O. N.; Petrosyan, V. G.; Martirosyan, I. A.; Ryskov, A. P. (Russian journal of genetics, 2006)
Using multilocus DNA fingerprinting with microsatellite probes (CAC) sub(5), (GACA) sub(4), (GGCA) sub(4), and (GATA) sub(4), intraspecific variation of the Southeast Asian lizards belonging to the genus Leiolepis (bisexual species Leiolepis reevesii and triploid parthenogenetic species Leiolepis guentherpetersi) was first examined. The L. guentherpetersi lizards were characterized by monophyletic DNA fingerprint profiles for the loci detected by the (GACA) sub(4), (GGCA) sub(4), and (CAC) sub(5) probes, in terms of intrapopulation similarity index constituting S = 0.96. This was different from the individual-specific profiles of the lizards from bisexual, presumably parental species, L. reevesii (S = 0.6; P < 0.001). Genetic homogeneity of triploid L. guentherpetersi lizards at the loci examined serves as one of the arguments for the parthenogenetic nature of this species. Genetic variability of triploid parthenogenetic species L. guentherpetersi appeared to be comparable with that reported earlier for the Caucasian rock lizards of the genus Darevskia, namely, D. dahli, D. armeniaca, and D. unisexualis (P > 0.05). The results of DNA fingerprinting analysis of the same L. guentherpetersi samples with the (GATA) sub(4) hybridization probe were unexpected. Variability of parthenogenetic species L. guentherpetersi at the (GATA) sub(n) markers was remarkably higher than that at other DNA markers (S = 0.35; P = 3.08 x 10 super(-11)), being comparable to the variation of the (GATA) sub(n) DNA markers in bisexual species L. reevesii (P = 0.74). The reasons for high polymorphism of the (GATA) sub(n)-containing loci in L. guentherpetersi still remain unclear. This polymorhism is probably associated with high instability of the loci, which can be revealed by means of family analysis of parthenogenetic offspring.